Exfoliation of WS2 in the semiconducting phase using a group of lithium halides: a new method of Li intercalation. Issue 38 (25th August 2016) - Ghorai, Arup; Midya, Anupam; Maiti, Rishi; Ray, Samit K.
Abstract : Lithium halide assisted high yield synthesis of few layers of 2H phase semiconducting WS2 in organic solvents is reported. Abstract : Lithium halide assisted high yield synthesis of few layers of 2H phase semiconducting WS2 in organic solvents is reported. A group of lithium halides (LiCl, LiBr and LiI) has been employed for the first time to intercalate WS2 by using Li, followed by mild sonication to exfoliate in dispersive polar solvents. In contrast to the n -butyllithium ( n -BuLi) assisted exfoliation method, which yields only the metallic 1T phase on prolonged reaction (3–7 days) at higher temperatures, the proposed exfoliation method produces only semiconducting 2H WS2 in a much shorter time (5 minute sonication). A very high yield of 19 mg ml −1 has been obtained using LiI as an exfoliating agent due to its lower lattice energy compared to other alkali halides and the smaller size of the cation. Detailed microscopy and spectroscopic characterization reveals exfoliation of few layered WS2 with stoichiometric composition. Absorption and emission characteristics of the 2D WS2 layer exhibit a characteristic band edge and quantum confined transitions. As a proof-of-concept, we have successfully demonstrated photodetector devices comprising solution proccessed p-WS2 /n-Si heterojunctions, which behave as diodes with a high rectification ratio (>10 2 ) exhibiting a broad band photoresponse over the entire visible region.